2015
DOI: 10.1161/strokeaha.115.009318
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Lesions Double the Risk of Post-Thrombolytic Intracerebral Hemorrhage

Abstract: Background and Purpose-Cerebral white matter lesions (WMLs), a surrogate for small-vessel disease, are common in patients with stroke and may be related to an increased intracranial bleeding risk after intravenous thrombolysis in acute ischemic stroke. We aimed to investigate the risk of symptomatic intracerebral hemorrhage (sICH) in the presence of WMLs in a large cohort of ischemic stroke patients treated with intravenous thrombolysis. Methods-We included 2485 consecutive patients treated with intravenous th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 42 publications
1
29
1
Order By: Relevance
“…4, 6, 14, 15, 18, 19 The pooled incidence of poor outcome (defined as mRS>2 in three studies, 6, 14, 18 mRS≥2 in two studies 15, 19 ) was 47% (95%CI: 34%–60%) in the leukoaraiosis negative group compared to 64% (95%CI: 55%–74%) in the leukoaraiosis positive group. Pooled analysis of these studies demonstrated the odds of poor outcome at 3–6 month post-stroke to be significantly elevated in those with evidence of leukoaraiosis (OR: 2.02; 95%CI: 1.54–2.65, p<0.0001, Figure 3A), with significant statistical heterogeneity between studies (I 2 :73.5%, p=0.002).…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…4, 6, 14, 15, 18, 19 The pooled incidence of poor outcome (defined as mRS>2 in three studies, 6, 14, 18 mRS≥2 in two studies 15, 19 ) was 47% (95%CI: 34%–60%) in the leukoaraiosis negative group compared to 64% (95%CI: 55%–74%) in the leukoaraiosis positive group. Pooled analysis of these studies demonstrated the odds of poor outcome at 3–6 month post-stroke to be significantly elevated in those with evidence of leukoaraiosis (OR: 2.02; 95%CI: 1.54–2.65, p<0.0001, Figure 3A), with significant statistical heterogeneity between studies (I 2 :73.5%, p=0.002).…”
Section: Resultsmentioning
confidence: 98%
“…Six of the included studies (n=4976 patients, 71% of the whole included patient population in the systematic review) provided adjusted effect sizes of the independent association between leukoaraiosis and sICH in multivariable analyses (adjusted for different co-variates depending on each study’s results). 6, 13, 14, 16–18 In a pooled sensitivity analysis of these studies, there was a significant association between leukoaraiosis and sICH risk with an adjusted OR of 1.75 (95%CI: 1.35–2.27; p<0.0001) and moderately high degree of statistical heterogeneity (Figure 2C). …”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations